Bifenox: methyl 5-(2,4-dichlorophenoxy)-2-nitrobenzoate - Jeon, Youngeun (International Union of Crystallography, 2013)
In the title compound, the herbicide bifenox, C(14)H(9)Cl(2)NO(5), the dihedral angle between the dichlorobenzene and nitrobenzene rings is 78.79 (14)°. In the crystal, C—H⋯O hydrogen bonds give rise to a three-dimensional network structure in which there are both a π–π interaction [ring centroid separation = 3.6212 (16) Å] and a C—Cl⋯π interaction [Cl⋯ring centroid = 3.4754 (8) Å]. In addition, short Cl⋯Cl contacts [3.3767 (11) and 3.3946 (11) Å] are present.